Stress, psychological well-being and coping strategies among nurses in Sabah - Chin Lee Mei @ Mary Tan; Mohd Dahlan A. Malek; Ismail Maakip (Malaysian Journal of Medicine and Health Sciences, 2020)
Introduction: Nursing is a highly stressful profession that affects the nurses’ physical and mental health. To maintain the quality of health services, nurses must have physically and mentally healthy. Given this, the present study aimed to examine the level of Stress and Psychological Well-Being among nurses and the methods used by nurses to cope with them. Methods: A self-administered questionnaire was used to assess psychological well-being and coping strat¬egies with stress which include Ryff’s Psychological Well-Being (RPWB), Ways of Coping Questionnaire (WOCQ) and Nursing Stress Scales (NSS) for the data collection on 637 nurses in nine hospitals in Sabah. Results: The results revealed that the main Sources of Stress among nurses was Conflict with Other Nurses. Also, Purpose in Life was found to have the highest mean score in terms of psychological well-being among nurses. Furthermore, Positive Re¬appraisal was found to be employed by nurses in dealing with stress. The study also revealed there was relationship between the sources of stress and the psychological well-being among nurses. Conclusion: Thus, to reduce work stress among nurses, hospital administration should keep themselves aware of the work dynamics and address the negative conflict occurred in nurses as soon as it is recognized. Recognizing the impact of work stress and using the technique of coping plays a vital role in minimizing the stress of nurses.